Predictors of response to pegylated interferon treatment in HBeAg-negative patients with chronic hepatitis B - Guclu, Ertugrul; Tuna, Nazan; Karabay, Oguz; Akhan, Sila; Bodur, Hurrem; Ceylan, Bahadir; Tutuncu, Ediz (J Infection Developing Countries, 2014)
Introduction: Although pegylated interferons (pegIFNs) alpha-2a and alpha-2b have been used in chronic hepatitis B (CHB) treatment for many years, there are few studies concerning predictors of sustained virologic response (SVR) to pegIFN therapy. In this study, we aimed to investigate the predictors of response to pegIFN treatment in cases with HBeAg-negative CHB infection. Methodology: Seventeen tertiary care hospitals in Turkey were included in this study. Data from consecutively treated HBeAg-negative CHB patients, who received either pegIFN alpha-2a or alpha-2b, were collected retrospectively. SVR is defined as an HBV DNA concentration of less than 2,000 IU/mL six months after the completion of therapy Results: SVR was achieved in 40 (25%) of the 160 HBeAg-negative CHB patients. Viral loads in patients with SVR were lower compared to those with no SVR, beginning in the third month of treatment (p < 0.05). The number of cases with a decline of 1 log(10) IU/mL in viral load after the first month of treatment and with a serum HBV DNA level under 2,000 IU/mL after the third month of treatment was higher in cases with SVR (p < 0.05). The number of patients who had undetectable HBV DNA levels at week 48 among responders was significantly greater than among post-treatment virological relapsers (p < 0.05). Conclusions: Detection of a 1 log(10) decline in serum HBV DNA level at the first month of treatment and a serum HBV DNA level < 2000 IU/mL at the third month of therapy may be predictors of SVR.
Keywords: hepatitis B; interferon; sustained virological response; viral load